RES Investigation of the Aurora Basin Area (East Antarctica) - Cafarella, L.; Urbini, S.; Bianchi, C.; Zirizzotti, A.; Tabacco, I. E.; Forieri, A. (Terra Antartica Publication, 2008)
We analyse radio echo sounding (RES) data on the region between Lake Vostok and the Belgica Subglacial Highlands (East Antarctica) collected during four Italian expeditions (1995, 1999, 2001 and 2003). The survey aimed to define the morphological characteristics of the Aurora Trench and to aid the exploration of subglacial lakes. Published 199-201 3.8. Geofisica per l'ambiente N/A or not JCR open